The stellar fundamental metallicity relation: the correlation between stellar mass, star formation rate, and stellar metallicity - Looser, Tobias J; D’Eugenio, Francesco; Piotrowska, Joanna M; Belfiore, Francesco; Maiolino, Roberto; Cappellari, Michele; Baker, William M; Tacchella, Sandro (Monthly notices of the Royal Astronomical Society, 2024)
ABSTRACT We present observational evidence for a stellar fundamental metallicity relation (FMR), a smooth relation between stellar mass, star formation rate, and the light-weighted stellar metallicity of galaxies, analogous to the well-established gas-phase FMR. We use the non-parametric software ppxf to reconstruct simultaneously the star formation and chemical-enrichment history of a representative sample of galaxies from the local MaNGA (Mapping Nearby Galaxies at Apache Point Observatory) survey. We find that (i) the metallicity of individual galaxies increases with cosmic time and (ii) at all stellar masses, the metallicity of galaxies is progressively higher, moving from the starburst region above the main sequence (MS) towards the passive galaxies below the MS, manifesting the stellar FMR. The scatter is reduced when replacing the stellar mass $M_{*}$ with $M_{*}/R_{\rm e}$ (with $R_{\rm e}$ being the effective radius), in agreement with previous results using the velocity dispersion $σ _{\rm e}$, which correlates with $M_{*}/R_{\rm e}$. Our results point to starvation as the main physical process through which galaxies quench, showing that metal-poor gas accretion from the intergalactic medium/circumgalactic medium – or the lack thereof – plays an important role in galaxy evolution by simultaneously shaping both their star formation and their metallicity evolutions, while outflows play a subordinate role. This interpretation is further supported by the additional finding of a young stellar FMR, tracing only the stellar populations formed in the last 300 Myr. This suggests a tight co-evolution of the chemical composition of both the gaseous interstellar medium and the stellar populations, where the gas-phase FMR is continuously imprinted on to the stars over cosmic times.